THE EFFECTIVENESS OF LISTEN-READ-DISCUSS (LRD) AND GRAPHIC ORGANIZER COMBINATION TECHNIQUE TO TEACH READING COMPREHENSION OF DESCRIPTIVE TEXT - Maemun, Akhmad; Fitriati, Sri Wuli; Farida, Alief Noor (ELT Forum: Journal of English Language Teaching, 2018)
This paper is to investigate the effectiveness of the combination technique of LRD(Listen-Read-Discuss) and graphic organizer in teaching reading comprehension. Iused quasi-experimental design in this research. The population of this study was theeighth year students of SMP Negeri 1 Dukuhwaru,Tegal in the academic year of2016/2017. Meanwhile, the sample consisted of 70 students from two classes. Thestudy was started by giving pre-test, treatments, and post-test to both groups. Theexperimental group (VIII D) was taught by LRD and graphic organizer combinationtechnique, while the control group (VIII F) was taught by using conventionalmethod. The data were obtained by giving a reading test to both groups. In addition,the questionnaire and observation were also conducted for the experimental groupto obtain more data. The result of the study indicated that the group taught by LRDand graphic organizer combination technique has better score in the test than thegroup taught by conventional method. In the pretest, the mean score of the controlgroup was 56.65 and the experimental group was 58.11. The mean of posttest ofexperimental group (82.05) was higher than control groups (70.11). Then, the t-testshowed that the tvalue (5.756) was higher than ttable (1.998). It can be concludedthat the working hypothesis is accepted. It means that there is a significant differenceof effectiveness and reading comprehension achievement in reading descriptive textof students who are taught by LRD and graphic organizer combination techniqueand those who are not taught by using that technique. Therefore, thatcombination technique is effective and convenient for students to improve theirachievement reading comprehension of descriptive text.